HUBUNGAN ANTARA RELIGIUSITAS DAN KESEJAHTERAAN PADA MASYARAKAT BANJAR, KALIMANTAN SELATAN - Sadewa, Manik Mutiara; Budiman, Mochammad Arif; Mairijani, Mairijani (IAIN Antasari, 2015)
In Islam, there is a positive relationship and correlation between religiosity (religious) and welfare (Sura 7:96; 65: 2-4). However, different from the conventional concept which relates only to the dimensions of the material welfare alone, welfare in the concept of Islam has a wide spectrum and multidimensional. Unfortunately, so far not many empirical studies conducted to conï¬ rm this relationship in the life of the Muslim community. This study was conducted using a survey on Muslim communities in South Kalimantan which is known as Islamic identity and a strong adherence to the teachings of Islam. Variables of religiosity and welfareare measured by a variety of dimensions and indicators which are developed from the concept of Maqasid al-Shariahand further processed by the method of principal component analysis (PCA) and conï¬rmatory factor analysis (CFA). Data analysis is using Structural Equation Modeling (SEM) showed religiosity in South Kalimantan Muslim community positively correlated with the level of welfare.